Heart Procurement from a Donor on Venovenous ECMO Support. Issue 3 (May 2016) - Singh, Gopal; Tsukashita, Masaki; Biscotti, Mauer; Costa, Joseph; Lambert, Daniel; Bacchetta, Matthew; Takayama, Hiroo
Abstract : We report the case of a 37-year-old woman with acute respiratory distress syndrome and became a candidate for organ donation after anoxic brain injury and was on a venovenous extracorporeal membrane oxygenation (VV-ECMO) support. On preoperative evaluation and gross examination, the donor's heart was acceptable for heart transplantation to a 62-year-old female patient with a history of nonischemic cardiomyopathy with a HeartMate II mechanical assist device. Orthotopic heart transplantation was successfully performed in the recipient. We report a case that suggests that the procurement of a heart from a donor on ECMO support can potentially expand the donor heart pool in carefully selected patients.